2016
DOI: 10.1002/anie.201600419
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Hydrophilicity and Hydrophobicity of the Respective Cation and Anion: Reversible Phase Transfer of Ionic Liquids

Abstract: The separation and recycling of catalyst and cocatalyst from the products and solvents are of critical importance. In this work, a class of functionalized ionic liquids (ILs) were designed and synthesized, and by tuning the hydrophilicity and hydrophobicity of cation and anion, respectively, these ILs could reversibly transfer between water and organics triggered upon undergoing a temperature change. From a combination of multiple spectroscopic techniques, it was shown that the driving force behind the transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 84 publications
3
54
0
Order By: Relevance
“…All the [PEG m (mim) 2 ][NTf 2 ] 2 ILs were synthesized, puried, and characterized according to the procedures described previously. 37 The purities of these ILs were found to be higher than 99.0 wt%, as determined by quantitative 1 H NMR measurements. 38 Myoglobin (Mb) from horse heart, hemoglobin (Hb) from bovine blood, albumin from bovine serum (BSA), trypsin from bovine pancreas, horseradish peroxidase (HRP) and lysozyme (Lyz) from chicken egg white, cytochrome c (Cyt.c) and papain were purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…All the [PEG m (mim) 2 ][NTf 2 ] 2 ILs were synthesized, puried, and characterized according to the procedures described previously. 37 The purities of these ILs were found to be higher than 99.0 wt%, as determined by quantitative 1 H NMR measurements. 38 Myoglobin (Mb) from horse heart, hemoglobin (Hb) from bovine blood, albumin from bovine serum (BSA), trypsin from bovine pancreas, horseradish peroxidase (HRP) and lysozyme (Lyz) from chicken egg white, cytochrome c (Cyt.c) and papain were purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 88%
“…These ILs are a new appealing group of liquid materials and have found various applications in chemical synthesis, 33 biomass dissolution, 34 stabilization of proteins 35 and nanoparticles. 36 In a recent work, 37 we have designed, synthesized and characterized a new class of PEG-functionalized imidazolium ILs [PEG m (mim) 2 ][NTf 2 ] 2 (with PEG average molecular weight m ¼ 200, 400, 600, 800 and 1000), and their chemical structures were shown in Chart 1. It was found that these ILs exhibited unique LCST phase behavior in water.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels, made of varieties of polymers, are classified as “smart” materials, owing to their responsiveness to external stimuli such as pH and temperature . Hydrogels with complex structures such as core–shell, hollow, Janus, and multilayered structures have many applications in cosmetics, drug delivery, oil recovery, and cell encapsulation .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels, made of varieties of polymers, are classified as "smart" materials, owing to their responsivenesst oe xternal stimuli such as pH and temperature. [1,2] Hydrogels with complex structures such as core-shell, hollow,J anus, and multilayered structuresh ave many applications in cosmetics, [3,4] drug delivery, [5,6] oil recovery, [7][8][9] and cell encapsulation. [1,10] Compared with previous microfluidics methods for creatingd ouble or higher order emulsions, whichr elied on complicated microfluidic devices with accurate surface wettability that is tedious and difficult to construct, [11][12][13][14] the phase separationt echnique promises to be af acile and reliable way to produce monodisperse, high-order emulsions with complex structures on the order of one to hundreds of micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive materials have attracted increasing attention in a variety of areas, such as drug delivery, 1 sensing, 2 coating, 3 and catalysis. 4 Up to now, pH, 5 temperature, 6 light, 7 redox agents 8 and CO 2 9 have been used as external stimuli for stimuli-responsive materials. Among these external stimuli, the light trigger is of great importance and has many advantages, 10 since no "invasion" is introduced into the system during the stimuli-responsive process, and the optical signal is easy to obtain with stability and reliability.…”
Section: Introductionmentioning
confidence: 99%